2005
DOI: 10.1111/j.1468-1293.2005.00278.x
|View full text |Cite
|
Sign up to set email alerts
|

Osteoprotegerin and bone turnover markers in heavily pretreated HIV‐infected patients

Abstract: ObjectivesTo characterize osteoprotegerin (OPG) levels, bone remodelling and bone mineral density (BMD) in heavily pretreated HIV-infected patients on antiretroviral therapy, and to evaluate the clinical factors associated with bone density decline. MethodsHeavily pretreated (45 years) HIV-positive patients were enrolled in this cross-sectional, observational study, which was based on a total body bone densitometry examination and a comprehensive evaluation of bone and mineral parameters. ResultsSixty-eight pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
2
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 29 publications
4
26
2
2
Order By: Relevance
“…Similar results were reported in a US population of seropositive teenagers and young adults, employing a cut-off for serum 25(OH)D of 15 ng/mL, demonstrating a prevalence of 87% of hypovitaminosis D (12). Seminari, in Italy, found serum 25(OH)D levels of less than 18 ng/mL in 81,25% of the patients, aged 41 years, who were on ART and had been losing bone (24). Similar prevalence (86%) was described by Aparicio and cols.…”
Section: Possible Mechanisms Of Vitamin D Deficiency In Hiv-infected supporting
confidence: 63%
See 1 more Smart Citation
“…Similar results were reported in a US population of seropositive teenagers and young adults, employing a cut-off for serum 25(OH)D of 15 ng/mL, demonstrating a prevalence of 87% of hypovitaminosis D (12). Seminari, in Italy, found serum 25(OH)D levels of less than 18 ng/mL in 81,25% of the patients, aged 41 years, who were on ART and had been losing bone (24). Similar prevalence (86%) was described by Aparicio and cols.…”
Section: Possible Mechanisms Of Vitamin D Deficiency In Hiv-infected supporting
confidence: 63%
“…Before antiretroviral treatment was introduced, few studies had indicated that bone metabolism was affected in HIVpositive patients, although it has recently been confirmed that infected patients present a higher risk of low bone mass and osteoporosis. Despite the fact that that was initially attributed to the use of these medications, it was later confirmed that its origins were due to a series of factors, one of the main ones being metabolic dysfunction of vitamin D (7,8,24).…”
mentioning
confidence: 99%
“…The multiple factors listed as promoters of osteopenia include direct effects of the virus on osteogenic cells; persistent activation of proinflammatory cytokines, mainly TNF-α and interleukin-1; changes in vitamin D metabolism, with deficit of 1,25 di-hydrovitamin D, as well as the involvement of mitochondrial abnormalities related with lactic acidemia and the development of opportunistic diseases [4,5].…”
Section: Osteopenia/osteoporosismentioning
confidence: 99%
“…22 Each of these metabolic abnormalities is well documented in HIV-positive patients and may be due to HIV infection or to treatment with drugs such as protease inhibitors as part of highly active antiretroviral therapy (HAART). [23][24][25] In a recent meta-analysis, 15% of HIV-infected patients had osteoporosis, for a pooled odds ratio of 3.7 compared to HIV-negative controls. 26 In a separate study, vitamin D insufficiency (81%) and secondary hyperparathyroidism (26%) were other frequent findings among HIV patients treated with HAART for more than 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…26 In a separate study, vitamin D insufficiency (81%) and secondary hyperparathyroidism (26%) were other frequent findings among HIV patients treated with HAART for more than 5 years. 25 Osteoporosis, hyperparathyroidism, elevated calcium phosphate product, chronic renal failure, and diabetes mellitus have all been associated with medial as well as intimal calcification. 2,22,27,28 Although we have little evidence of patients in this study suffering from these conditions, many were HIV-infected and heavily exposed to HAART.…”
Section: Discussionmentioning
confidence: 99%